Current kinematics and dynamics of Africa and the East African Rift System. Issue 6 (16th June 2014) - Stamps, D. S.; Flesch, L. M.; Calais, E.; Ghosh, A.
Abstract Although the East African Rift System (EARS) is an archetype continental rift, the forces driving its evolution remain debated. Some contend buoyancy forces arising from gravitational potential energy (GPE) gradients within the lithosphere drive rifting. Others argue for a major role of the diverging mantle flow associated with the African Superplume. Here we quantify the forces driving present‐day continental rifting in East Africa by (1) solving the depth averaged 3‐D force balance equations for 3‐D deviatoric stress associated with GPE, (2) inverting for a stress field boundary condition that we interpret as originating from large‐scale mantle tractions, (3) calculating dynamic velocities due to lithospheric buoyancy forces, lateral viscosity variations, and velocity boundary conditions, and (4) calculating dynamic velocities that result from the stress response of horizontal mantle tractions acting on a viscous lithosphere in Africa and surroundings. We find deviatoric stress associated with lithospheric GPE gradients are ∼8–20 MPa in EARS, and the minimum deviatoric stress resulting from basal shear is ∼1.6 MPa along the EARS. Our dynamic velocity calculations confirm that a force contribution from GPE gradients alone is sufficient to drive Nubia‐Somalia divergence and that additional forcing from horizontal mantle tractions overestimates surface kinematics. Stresses from GPE gradients appear sufficient to sustain present‐day rifting in East Africa; however, they are lower than the vertically integrated strength of the lithosphere along most of the EARS. This indicates additional processes are required to initiate rupture of continental lithosphere, but once it is initiated, lithospheric buoyancy forces are enough to maintain rifting.